(untitled) (West Sussex, 2016)
Research Methods in Intercultural Communication introduces and contextualizes the most important methodological issues in the field for upper-level undergraduate and graduate students. Examples of these issues are which paradigms and how to research multilingually, interculturally and ethnically.
Luận văn tốt nghiệp
Keywords: Giao tiếp đa văn hóa,Intercultural communication